2017
DOI: 10.1111/petr.12982
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoepidemiology of tacrolimus in pediatric liver transplantation

Abstract: AEs during immunosuppressive treatment with tacrolimus are very common. We retrospectively evaluated FK safety and efficacy in a large pediatric liver transplant cohort in Latin America. During 2-year follow-up, we analyzed data from patients who underwent liver transplantation over the period 2010-2012 and recorded FK exposure, AEs, and AR episodes. AEs were classified according causality and severity. Tacrolimus exposure before and during AE was compared using Wilcoxon matched-pairs test. Kaplan-Meier curves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…In this study, we found that children treated with CNI showed significantly lower serum magnesium levels and that they were significantly more likely to develop hypomagnesemia. This is in line with previous findings in children [ 31 , 32 , 33 , 34 ] and adults [ 21 ]. In adults and animal models, it was shown that hypomagnesemia is caused by renal magnesium wasting [ 20 , 21 , 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we found that children treated with CNI showed significantly lower serum magnesium levels and that they were significantly more likely to develop hypomagnesemia. This is in line with previous findings in children [ 31 , 32 , 33 , 34 ] and adults [ 21 ]. In adults and animal models, it was shown that hypomagnesemia is caused by renal magnesium wasting [ 20 , 21 , 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…To the best of our knowledge, this is the first study exploring the demographics and outcomes of CNI intoxication using VigiBase™. The results from VigiBase™ affirm those obtained from previous epidemiological studies regarding the toxicity of CNIs [23,60,61]. Due to underreporting or unreported cases, the actual proportion of CNI intoxications in ICSRs at the global level remains unknown.…”
Section: Retrospective Analysis Of Cni Intoxications From Vigibase™ V...supporting
confidence: 79%
“…The present study was originally intended to evaluate a new immunosuppressive protocol in our hospital including the utilization of induction therapy to minimize the administration of steroids in pediatric patients who received the first liver transplantation. This study is comprised of patients included in a previous report 13 .…”
Section: Study Populationmentioning
confidence: 99%
“…Despite close individual monitoring, ADR and AR episodes are still detrimental to the patient´s quality of life. Limited information is available in the literature regarding the causes of inter-individual variability in tacrolimus pharmacodynamics in pediatric patients, and particularly in Latin-American liver transplant patients 12,13 . Specifically, identification of risk factors for AR and ADR to tacrolimus may help in reducing the frequency of complications after liver transplantation, and hence minimize the risk of graft loss, non-compliance, and death 14 .…”
Section: Introductionmentioning
confidence: 99%